Association between hyperlipidemia and postoperative delirium risk: a systematic review and meta-analysis - Qiu, Li-quan; Song, Jian-li; Zhang, Li-cai; Fan, Bin; Li, Qiang; Lu, Bin; Chen, Guan-yu (Frontiers in Aging Neuroscience, 2025)
IntroductionThe association between hyperlipidemia and its potential role as a risk factor for postoperative delirium (POD) remains unclear.MethodsWe systematically searched PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov to identify studies meeting the inclusion criteria. Outcomes of interest included comparisons of blood lipid levels between POD and non-POD (NPOD) patients, the association between hyperlipidemia and POD risk, and the predictive value of hyperlipidemia for POD.ResultsA total of nine studies involving 4,686 patients were included in the meta-analysis. Pooled analysis revealed that hyperlipidemia was significantly associated with an increased risk of POD (OR = 1.47; 95% CI 1.13–1.91; P = 0.004;) compared to patients without hyperlipidemia. Patients with POD exhibited significantly higher levels of total cholesterol (TC) (weighted mean difference [WMD] = 0.31; 95% CI 0.03–0.59; P = 0.030), triglycerides (TG) (WMD = 0.37; 95% CI 0.03–0.71; P = 0.033), and low-density lipoprotein cholesterol (LDL-C) (WMD = 0.09; 95% CI 0.01–0.17; P = 0.023) compared to NPOD patients. In contrast, high-density lipoprotein cholesterol (HDL-C) levels were significantly lower in POD patients (WMD = −0.07; 95% CI −0.12 to −0.01; P = 0.026). Insufficient evidence was available to summarize the area under the curve (AUC) results.ConclusionsBlood lipid levels were significantly elevated in POD patients compared to NPOD patients. Hyperlipidemia was significantly associated with an increased risk of POD, highlighting its potential role as a risk factor.